P037 Nonclinical pharmacokinetics and absorption, distribution, metabolism, and excretion properties of MORF-057 support its clinical development as an oral selective α4β7 integrin inhibitor. (27th May 2021) - Jones, J; Lee, D; Smukste, I; Cui, D; Bursavich, M G; Troast, D; Zhong, C; Wong, J E; Mangada, M M; Bain, G; Lippa, B; Ray, A S; et al.
Abstract: Background: MORF-057 is a potent and selective small molecule inhibitor of the α 4 β 7 integrin. Using a receptor occupancy (RO) assay under physiologically relevant conditions, MORF-057 achieves 90% α 4 β 7 RO at approximately 10 nM in human whole blood. The current studies evaluate nonclinical pharmacokinetics (PK) and properties of absorption, distribution, metabolism, and excretion (ADME) to enable dose/exposure projection to humans. Methods: PK studies were conducted in mouse, rat, dog, and monkey following intravenous (IV) and oral administration. ADME studies were conducted in vitro and in rats using carbon-14 [14C] labeled MORF-057. MORF-057 levels were quantified using liquid chromatography coupled with tandem mass spectrometry. Human PK was predicted based on body weight allometry, well-stirred and semi-physiological models. Results: MORF-057 exhibited low to moderate clearance (CL) in animals with species dependent volume of distribution (Vdss) resulting in half-lives of 1.1 to 2.7 hours (Table 1). Following an oral dose, absorption was high with bioavailability ranging from 15% to 49%. MORF-057 is highly protein bound and distribution of [14C]MORF-057 derived radioactivity in rat was predominantly in the small intestine wall, liver, and stomach wall. Rifampin, an inhibitor of organic anion transporting polypeptides, decreased MORF-057 clearance by 3-fold in monkeys suggesting MORF-057 elimination involves hepatic uptake transport. MORF-057 is further cleared via CYP3A metabolism followed by biliary/fecal elimination of metabolites. MORF-057 is predicted to have moderate bioavailability (40%) and CL (6.5 mL/min/kg) in humans. Wajima transformation shows good agreement of the normalized PK across animal species, with a predicted human concentration-time profile supporting >90% α 4 β 7 RO at trough following 200 mg twice daily dose (Figure 1). Conclusion: These data demonstrate that MORF-057 is well absorbed and PK properties in animals support the potential for achieving high α4β7 RO following oral administration in humans. These nonclinical results provided a basis for the progression of MORF-057 into a first-in-human Phase 1 clinical study assessing safety, pharmacokinetics, and receptor occupancy (results being reported separately).